A novel inchworm piezoelectric actuator using two-stage amplification mechanism with high speed: design, modeling, and experimental evaluation. (1st May 2023) - Yu, Simiao; Liang, JiaYu; Yang, Fan; Wang, Haitao; Liu, Xianglong; Xu, Chao; Wang, Zhen; Xu, Dongmei
Abstract: The inchworm piezoelectric actuator has a wide application prospect in the field of precision instruments. However, in view of the complex structure of the existing inchworm piezoelectric actuator and the far distance between the driving feet of the actuator, it is difficult to realize alternate driving and the high output speed of the driving feet, etc. In this paper, an inchworm piezoelectric linear actuator based on two-stage amplification mechanism is designed, which amplifies the output displacement of the driving feet by two-stage amplification mechanism, and improves the driving efficiency of the actuator stator by the way of alternating driving. We present an inchworm piezoelectric actuator with three piezoelectric stacks and a two-stage amplification mechanism, which is simple in structure design, compact in actuator structure and easy to realize alternate driving. The kinematics and dynamics models of the inchworm piezoelectric actuator are established by analyzing the flexible hinge and its structure with the pseudo-rigid body method. The length of the lever structure and the angle of the triangular structure of the piezoelectric actuator are solved by kinematics, and the natural frequency of the whole structure is calculated by dynamics. Through finite element analysis, the simulation magnification ratio of the piezoelectric actuator is obtained, so as to evaluate and verify the theoretical calculation and further optimize the structure. The experimental results show that the inchworm piezoelectric linear actuator using two-stage amplification mechanism has a high driving speed of 5.53 mm s −1 under voltage of 135 V and frequency of 70 Hz.